The Pain Medicine Curriculum Framework-structured integration of pain medicine education into the medical curriculum - Shipton, Elspeth; Steketee, Carole; Visser, Eric (Frontiers in Pain Research, 2023)
Medical practitioners play an essential role in preventing pain, conducting comprehensive pain assessments, as well as promoting evidence-based practices. There is a need for the development of innovative, interprofessional and integrated pain medicine curricula for medical students. The Pain Medicine Curriculum Framework (PMCF) was developed to conceptualise a purposeful approach to the complex process of curriculum change and to prioritise the actions needed to address the gaps in pain medicine education. The PMCF comprises four dimensions: (1) future healthcare practice needs; (2) competencies and capabilities required of graduates; (3) teaching, learning and assessment methods; and (4) institutional parameters. Curricula need to meet the requirements of registration and accreditation bodies, but also equip graduates to serve in their particular local health system while maintaining the fundamental standards and values of these institutions. The curriculum needs to connect knowledge with experience and practice to be responsive to the changing needs of the increasingly complex health system yet adaptable to patients with pain in the local context. Appropriate learning, teaching and assessment strategies are necessary to ensure that medical practitioners of the future develop the required knowledge, skills and attitudes to treat the diverse needs of patients’ experiencing pain. The historical, political, social and organisational values of the educational institution will have a significant impact on curriculum design. A more formalised approach to the development and delivery of a comprehensive pain medicine curriculum is necessary to ensure that medical students are adequately prepared for their future workplace responsibilities.